The Filipino-American war in Leyte and Samar the local fronts mirror-image of the national experience - Amascual, Pablo U., III (2003)
The Filipino-American War (1899-1913) was the bloodiest conflict at the turn of the 20th century. It was known as America's first colonial war, and the Filipinos' second war for independence. The war was the inevitable consequence of two colliding aspirations: the American's imperial design in East Asia and the Filipinos' thirst for independence after centuries of colonial subjugation. The war saw many atrocities committed by the American military forces against both Filipino combatants and non- combatants. The sudden attack by the Americans, triggered by a minor shooting incident in a checkpoint, caught the Filipino forces unprepared so that many areas within and surrounding Manila were quickly overrun. The countless number of deaths and massive devastation that followed was justified by the Americans as a response to an act of war. Yet these same Americans absolutely abhorred the surprise attack on an unsuspecting garrison in Balangiga. The employment of guerrilla tactics by the Filipino forces in the Luzon area minimized the advantages of the Americans in conventional warfare. The people in the Leyte and Samar islands also witnessed the guerrilla warfare being employed successfully by both General Ambrosio Mojica and General Vicente Lukban. The establishment of concentration camps to hamlet noncombatants was another atrocity committed by the Americans to deprive the Filipino soldiers of the support of the masses. This was done not just in many parts of Luzon, but also in Samar. Many more innocent civilian lives were lost in these camps due to starvation and disease. The absence of support by the educated and wealthy class contributed greatly to the defeat of the Filipinos. When one faction of idealistic and independence-loving Filipinos would wage war against a colonizer, the other group of pragmatic and peace-loving ilustrados would cooperate with the invaders to maintain the status quo. Mabini himself decried the lack of patriotism among the Filipino elite in the Tagalog region. Such was the same attitude of the rich in Leyte towards American colonization. The non-regular combatants, who were branded as bandits. continued the fight against the Americans even after the official surrender of regular Filipino forces under Aguinaldo. In Luzon, the fight for independence was continued by resistance leaders like Macario Sakay. In Leyte and Samar. the Putajanes and DiosDios inflicted considerable casualty and damage against the Americans and Filipino collaborators alike. The U.S. Government called the pockets of resistance as an insurrection. Such "insurrection" lasted until 1907 in Leyte and until 1910 in Samar. Indeed, the experiences during the Filipino-American War in Luzon, where much of national history is focused, are the very same scenarios that were observed in the Leyte and Samar areas.
Includes bibliographical references.